2013
DOI: 10.1364/oe.21.009113
|View full text |Cite
|
Sign up to set email alerts
|

Strong absorption and selective emission from engineered metals with dielectric coatings

Abstract: We demonstrate strong-to-perfect absorption across a wide range of mid-infrared wavelengths (5-12µm) using a two-layer system consisting of heavily-doped silicon and a thin high-index germanium dielectric layer. We demonstrate spectral control of the absorption resonance by varying the thickness of the dielectric layer. The absorption resonance is shown to be largely polarization-independent and angle-invariant. Upon heating, we observe selective thermal emission from our materials. Experimental data is compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 18 publications
1
79
0
Order By: Relevance
“…The superabsorber comprises a highly absorbing (large j) material and a transparent medium. We note, in passing that very recently compact absorbers in a planar geometry have been also reported by Kats et al 42 and Streyer et al 43 with designs that rely on the mutual optical properties of two lossy materials in the former work or a high index dielectric and an engineered metal of e $ À1 in the latter work. In our proposed compact design, the underlying mechanism is a PC effect, where absorption is facilitated by a reflectionless funneling to a photonic-crystal mode, with a highly lossy Floquet-Bloch phase.…”
Section: Practically Realizable Superabsorber Designssupporting
confidence: 54%
“…The superabsorber comprises a highly absorbing (large j) material and a transparent medium. We note, in passing that very recently compact absorbers in a planar geometry have been also reported by Kats et al 42 and Streyer et al 43 with designs that rely on the mutual optical properties of two lossy materials in the former work or a high index dielectric and an engineered metal of e $ À1 in the latter work. In our proposed compact design, the underlying mechanism is a PC effect, where absorption is facilitated by a reflectionless funneling to a photonic-crystal mode, with a highly lossy Floquet-Bloch phase.…”
Section: Practically Realizable Superabsorber Designssupporting
confidence: 54%
“…[13] More recently, several studies demonstrated strong resonant/absorptive characteristics from double-layer thin-film coatings [14,15] or metalinsulator-metal triple-layer [16,17] or multilayer [18,19] coatings in microwave, infrared (IR) spectrum and beyond. Particularly, in a recent work [14] [2,4,[20][21][22] spectral characteristics.…”
mentioning
confidence: 99%
“…Metasurfaces-based optics is an attractive alternative approach at these spectral regions which are used by thermal imagers. In addition, metasurfaces can be utilized for modifying the spectral properties of thermal emitters [104,105] with great potential for electric power generation from heat sources.…”
Section: Discussion Outlook and Challengesmentioning
confidence: 99%